Sikap Bahasa Penutur Shimakutuba Dialek Uchinaguchi Di Prefektur Okinawa - Reny Wiyatasari (Diponegoro University, 2019)
(Title: Language Attitudes Of The Speakers Of Uchinaguchi Dialect, Shimakutuba Language In Okinawa Prefekture) This study aims to determine the language attitude of the speakers of the Uchinaguchi dialect, one of the dialects in Shimakutuba which is the language used in the Okinawa islands. Shimakutuba is one of the languages in the world set by UNESCO as an endangered language. Because the theme of this research is focused on language attitudes which is one of the topics in sociolinguistic studies, the data are collected using the questionnaire method through distributing questionnaires to respondents who are considered representative representing the research population and also using literature study methods. Then the data were analyzed using descriptive methods. Based on the results of the questionnaire, it was found that the language attitude shown by speakers of Shimakutuba was divided into two, namely positive attitudes and negative attitudes. A positive attitude consists of positive active and positive passivity.